2021
DOI: 10.1177/21649561211010129
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use by Patients From the Gulf Region Seen in the International Practice of a Tertiary Care Medical Center

Abstract: Background Patients from various countries may have unique patterns of using complementary and alternative medicine (CAM) and unique reasons for using it. Objective Our objective was to assess the use of CAM among patients from the Gulf region attending the Executive and International Health Program of the Department of General Internal Medicine at Mayo Clinic in Rochester, Minnesota. Methods This cross-sectional survey was administered to all patients who were from the Gulf region and were undergoing outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In contrast to this, this study and other current studies found that people with high socioeconomic status were more likely to use TCM. Studies have persistently shown that CAM/TCM users are more likely to be female, 36–41 better educated, 39 , 42 , 43 as well as to have higher income 44 , 45 and occupational status. 46 We found that patients with health insurance and those who lived in urban areas were more likely to think TCM is multi-effective, and other studies 17 , 47 came to the same conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this, this study and other current studies found that people with high socioeconomic status were more likely to use TCM. Studies have persistently shown that CAM/TCM users are more likely to be female, 36–41 better educated, 39 , 42 , 43 as well as to have higher income 44 , 45 and occupational status. 46 We found that patients with health insurance and those who lived in urban areas were more likely to think TCM is multi-effective, and other studies 17 , 47 came to the same conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, older people find TCM to be more useful than younger people. 17 , 39 , 42–45 One reason for this finding might be that they have a higher recognition of traditional Chinese culture because they primarily used TCM when there was a shortage of doctors and medicine in China and TCM played an even more important role in primary health care in the 1950s. On the other hand, the medical conditions of older patients were worse, which seems to be one of the factors affecting their views on the use of TCM in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have delved into the incidence of CAM use, healthcare professionals' attitudes toward CAM, and communication patterns that differ by nationality and cancer type [3][4][5][6][7][8]. In Korea, up to 85% of patients with cancer use one or more types of CAM [9].…”
Section: Introductionmentioning
confidence: 99%
“…[11] I-CAM-Q is designed to reduce questionnaire bias and provide accurate international comparisons of CAM usage among populations. Several I-CAM-Q studies have already been published, [2,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] with the possibility of more international comparative research to be conducted in the future.…”
Section: Introductionmentioning
confidence: 99%